2013
DOI: 10.1021/np400218z
|View full text |Cite
|
Sign up to set email alerts
|

Chenopodolin: A Phytotoxic Unrearranged ent-Pimaradiene Diterpene Produced by Phoma chenopodicola, a Fungal Pathogen for Chenopodium album Biocontrol

Abstract: A new phytotoxic unrearranged ent-pimaradiene diterpene, named chenopodolin, was isolated from the liquid culture of Phoma chenopodicola, a fungal pathogen proposed for the biological control of Chenopodium album, a common worldwide weed of arable crops such as sugar beet and maize. The structure of chenopodolin was established by spectroscopic, X-ray, and chemical methods as (1S,2S,3S,4S,5S,9R,10S,12S,13S)-1,12-acetoxy-2,3-hydroxy-6-oxopimara-7(8),15-dien-18-oic acid 2,18-lactone. At a concentration of 2 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 32 publications
2
49
1
Order By: Relevance
“…Assayed at 4 Â 10 À3 M on punctured detached leaves, 3 proved to be active in particular on Sonchus arvensis, causing the fast appearance of wide necrosis (scored +++) and on Urtica dioica and Parietaria officinalis, with smaller but still evident necrosis (+). This result differed from the non-toxic activity observed previously when 3 was tested on different plants (Mercurialis annua, Cirsium arvense and Setaria viride) using the same bioassay (Cimmino et al, 2013a). The different behavior could be due to different plant sensitivity.…”
Section: Resultscontrasting
confidence: 88%
See 3 more Smart Citations
“…Assayed at 4 Â 10 À3 M on punctured detached leaves, 3 proved to be active in particular on Sonchus arvensis, causing the fast appearance of wide necrosis (scored +++) and on Urtica dioica and Parietaria officinalis, with smaller but still evident necrosis (+). This result differed from the non-toxic activity observed previously when 3 was tested on different plants (Mercurialis annua, Cirsium arvense and Setaria viride) using the same bioassay (Cimmino et al, 2013a). The different behavior could be due to different plant sensitivity.…”
Section: Resultscontrasting
confidence: 88%
“…The preliminary investigation of its 1 H and 13 C NMR spectra (Table 4) showed that they are very similar to those of chenopodolin (Cimmino et al, 2013a). Indeed, 3 showed the signal systems typical of the tetracyclic ent-pimaradiene lactone and also those corresponding to the a,b-unstaturated ketone at C(6)-C(8), the vinyl and the tertiary methyl both bonded to C-13, as well as the acetoxy groups at C-1 and C-12.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…21 Cavoxin, 10, and cavoxone, 11, and chenopodolin, 12; chenopodolan C, 13; and 6-hydroxymellein, 14 ( Figure 2), were isolated, respectively, from the culture filtrates of Phoma cava 22 and Phoma chenopodiicola. 23,24 Cytochalasins A, 15, and B, 16, and deoxaphomin, 17 (Figure 2), were isolated from the solid culture of Pyrenophora seminiperda. 25 All the above cited fungal metabolites were freshly isolated from the fungal cultures according to the protocols reported in the literature and were identified by 1 H NMR and electrospray ionization mass spectrometry (ESI MS), comparing these data with those previously described.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%